Productivity and stress resistance of the Omsk spring barley varieties in the southern forest-steppe of Western Siberia - P. N. Nikolaev; O. A. Yusova; N. I. Aniskov; I. V. Safonova (Зерновое хозяйство России, 2022)
Newly developed varieties should be not only highly productive, but also adaptable. In this regard, the Omsk Agricultural Center is certainly one of the leaders in spring barley breeding (23 varieties have been created). New varieties should meet both the current needs of agricultural producers and agro-technological requirements in accordance with the achievements of science and production. In this regard, the purpose of the current study was to determine adaptability parameters of the Omsk barley varieties. There have been presented the study results of 2015–2019. The objects of the study were the two-row hulled varieties and lines ‘Omsky 95’ (standard), ‘Sasha’, ‘Podarok Sibiri’, ‘Omsky 100’, ‘Omsky 101’, ‘Medikum 4867’, ‘Nutans 4883’, ‘Nutans 4812’; the multi-row hulled varieties and lines ‘Omsk 99’ (standard), ‘Rikotense 4885’, ‘Pallidum 4861’; the multi-row hulles varieties and lines ‘Omsk golozerny 2’ (standard), ‘Omsk golozerny 4’. There have been estimated such adaptability parameters as coefficient of adaptability (according to Zhivotkov), coefficient of responsiveness to favorable growing conditions (according to Zykin), stress resistance and compensatory ability (according to Goncharenko), adaptability (according to Baransky and Gryaznov), trait variability and coefficient of agronomic stability (according to Dospekhov). The final estimation of the response of varieties to cultivation conditions had to be carried out by the sum of the ranks, taking into account that the first rank was the highest. The studied varieties were characterized by productivity of 5.2±0.97 t/ha. There was identified a significant increase for all varieties (+0.13…+0.90 t/ha to standard). The greatest contribution to the yield variation was made by the year conditions (65%); the share of a variety genotype effect was 19%. According to the sum of ranks, for the southern forest-steppe of Western Siberia, the most adaptive varieties among the two-row hulled varieties and lines were ‘Sasha’, ‘Omsky 100’, ‘Omsky 101’ and ‘Nutans 4883’ (sum of ranks = 45–49). Among multi-row hulled varieties and lines it was ‘Rikotense 4885’ (sum of ranks = 46). Among the multi-row hulles varieties and lines they were ‘Omsk golozerny 2’ (standard), ‘Omsk golozerny 4’ (sum of ranks = 86 and 87).